Análise citogenética em acessos de Paspalum atratum (Poaceae) - Santos, Ana Caroline Casalvara dos (2013)
The genus Paspalum consists of about 400 species and essentially all are native to the Americas. The genus is economically important as many of its species are used as forage and pasture grasses. Due to its agronomic characteristics, some species of the genus are under evaluation to create new varieties throughout the direct selection of the genetic variablility or intra- or interspecific hybridization. In Paspalum, breeding is compromised by the ploidy level of the accessions and the mode of reproduction. Compatibility is generally found only among polyploidy accessions that are generally apomictics. Crosses are successful only between tetraploid accessions, but sexual female tetraploid accession is necessary. Despite of apomicts, polyploid accessions demand viable gametes to fertilizate the secondary nucleus to ensure the endosperm formation. Polyploidy, by the other hand, causes innumerous meiotic abnormalities that compromise the gamete viability. Among some Paspalum breeding programs in development in the country, we can cite that developed by the Embrapa Cattle-Southeast (CPPSE) situated in São Carlos, SP, Brazil. Among the several Paspalum species existing in the CPPSE collection, P. atratum has deserved attention due to its agronomic attributes. Paspalum atratum cv. Pojuca - Capim Pojuca (BRA 009610) is commercialized as variety in Brazil since 2004. However there is the necessity of development of new cultivars of this species. In this study, 14 accessions of P. atratum were analyzed by means of conventional methodology for the determination of their chromosome numbers and ploidy level, and the characterization of their meiotic behavior. It was found that all the accessions were tetraploid (2n = 4x = 40), derive from x = 10, and the chromosome number was in agreement with the previous data. In two accessions (BRA-023019 e BRA-023612) there was evidence of chromosome translocation an in other accession (BRA-0023353), dyads and triads were recorded. In the accession BRA-009687, a high frequency of meiotic abnormalities was found, while in the remaining, the meiotic abnormalities were rare or absent. The meiotic abnormalities detected in these accessions were related to irregular chromosome segregation typical of polyploids. Except for the four accessions tha presented especial abnormalities, the remaining ones (ten accessions) showed meiotic stability and, thus, potential to be released as cultivars or to participate in hybridization breeding program.